THE EFFECT OF PRODUCTS, LOCATION, PRICE AND PROMOTION ON CUSTOMER SATISFACTION (STUDY OF LOTTE WHOLESALE PEKANBARU) - Manatap, Nicholas Zelly; Lahinda, Laura (International Journal of Social Service and Research, 2024)
With the rapid growth of modern retail in Pekanbaru, where Lotte Grosir is one of the many existing retailers. The company must understand the importance of analyzing the marketing mix in relation to customer satisfaction to innovate and face competition. In this context, the marketing mix includes product, location, price and promotion, known as 4Ps. The purpose of this study is to analyze whether the components of the marketing mix have an impact on customer satisfaction, providing a descriptive overview of the current conditions and serving as a consideration for the company in improving customer satisfaction. This research uses a descriptive quantitative method. The sample selected in this study consist of Lotte Grosir Pekanbaru customers using the Simple Random Sampling method, resulting in 105 respondents who filled out the questionnaire. Data were analyzed using instrument test, validity test, reliability test, classical assumption test, multiple linear regression, and hypothesis testing with SPSS software. The result show that partially, the product variable (X1) does not significantly affect customer satisfaction (Y), while the location (X2), price (X3) and promotion (X4) variables have an impact on customer satisfaction (Y) variable. Other results indicate that simultaneously, product location, price and promotion have an influence on customer satisfaction with a coefficient of determination of 81.8% and the remaining 18.2% is influenced by others factors not examined in this study.